Strangers and kin : the American way of adoption - Melosh, Barbara (Harvard University Press, 2002)
'Strangers and Kin' is the history of adoption, a quintessentially American institution in its buoyant optimism, generous spirit and confidence in social engineering. Barbara Melosh tells the story of how married couples without children sought to care for and nurture other people's children as their own.